Research on spiritual struggles: A brief snapshot focusing on new horizons : Forschung über spirituelle Kämpfe: Eine kurze Momentaufnahme mit Fokus auf neue Horizonte - Exline, Julie J. (Spiritual care, 2024)
Many people experience spiritual struggles - experiences of tension, strain, or conflict around religious or spiritual matters. Empirical, psychological research on spiritual struggles has increased greatly in the past several decades. To date, much of the emphasis has been on developing and refining assessment tools and documenting links with emotional distress. Building on several recent reviews of spiritual struggle research (Pargament & Exline 2021; Pargament & Exline 2022) as well as our own recent projects on spiritual struggles, our aim in this article is to look toward the future: What are some promising new horizons in research on spiritual struggles? We will focus on four broad areas: 1) conceptualization, assessment, and methods, 2) connections between struggles and indicators of distress or problems, 3) how struggle might foster growth, and 4) clinical interventions.